Sibling Relations among Herders in Mărginimea Sibiului (Southern Transylvania) - Marin Constantin (Martor)
In southern Transylvania, sibling relations among herdsmen constitute a framework for organizing local shepherding practices. Our field data point to the importance of the brothers’ and sisters’ joint work in terms of the apprenticeship of young shepherds, the task rotation during seasonal transhumance, the sharing of their parents’ herds, and (as a result) the intergenerational continuity of pastoral ownership. Therefore, sibling relations among herders should be considered not only demographic evidence of consanguinity but more importantly a traditional pattern of sociality and economic mutual help, i.e., an institution. The functionality of such an institutional model is confirmed by the anthropological literature.